2008
DOI: 10.1002/humu.20717
|View full text |Cite
|
Sign up to set email alerts
|

Thermal instability of compound variants of carnitine palmitoyltransferase II and impaired mitochondrial fuel utilization in influenza-associated encephalopathy

Abstract: Influenza-associated encephalopathy (IAE) is characterized by persistent high fever, febrile convulsions, severe brain edema, and high mortality in otherwise apparently healthy individuals. We have reported that a large proportion of patients suffering from disabling or fatal IAE, with transiently elevated serum acylcarnitine during high fever, exhibit a thermolabile phenotype of compound homo-/heterozygous variants of carnitine palmitoyltransferase II (CPT II, gene symbol CPT2). We characterized the enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 48 publications
1
65
1
Order By: Relevance
“…Although the use of nonsteroidal anti-inflammatory drugs, such as aspirin and diclofenac sodium, is associated with a significant increase in the mortality rate of influenzaassociated encephalopathy (7,8), acetaminophen, which was used in the present case, may have had little effect on the development of encephalopathy. Furthermore, although the patient had a history of hypersensitive pneumonitis, we doubt that an allergic reaction affected the development of encephalopathy.…”
Section: Discussionmentioning
confidence: 70%
“…Although the use of nonsteroidal anti-inflammatory drugs, such as aspirin and diclofenac sodium, is associated with a significant increase in the mortality rate of influenzaassociated encephalopathy (7,8), acetaminophen, which was used in the present case, may have had little effect on the development of encephalopathy. Furthermore, although the patient had a history of hypersensitive pneumonitis, we doubt that an allergic reaction affected the development of encephalopathy.…”
Section: Discussionmentioning
confidence: 70%
“…While CPT2 gene polymorphisms do not decrease CPT II activity in normal physiological situations, the F352C variant alone has been reported to reduce CPT II activity by about 50% under certain conditions such as heat stress, fasting, acidosis, and seizures [9][10][11]17]. Shinohara et al has reported that the F352C variant is a statistically significant risk factor in patients with acute encephalopathy [12].…”
Section: Discussionmentioning
confidence: 99%
“…A congenital or acquired abnormality of mitochondrial fatty acid oxidation causes the accumulation of mini-plasmin in the cerebral capillaries and the proteolytical destruction of the blood-brain barrier in mice after influenza virus infection [9,18]. Intracellular ATP production is reduced by about 50% for the F352C variant compared to the wild type under severe conditions [9][10][11]17]. The suppression of intracellular ATP production weakens interactions between tight junction proteins of cerebral microvascular endothelial cells, leading to the destruction of brain homeostasis and brain edema [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations